PENEGAKAN HUKUM SITUS JUDI ONLINE DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Suhada, Dwi Raman; Erdiansyah, Erdiansyah; Andrikasmi, Sukamariko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Gambling through online sites has been regulated in Article 45 paragraph (3) of LawNumber 1 of 2024 concerning Electronic Information and Transactions which explains theprovision that every person who intentionally and without rights distributes, transmits and/ormakes accessible electronic information and/or electronic documents that have gamblingcontent as referred to in Article 27 paragraph (2) shall be sentenced to imprisonment for amaximum of ten years and/or a maximum fine of ten billion. However, what is known untilnow is that gambling through online sites is still widely available among the public and hasnot been resolved. This study aims to find out how the law enforcement of online gamblingsites in the Riau Regional Police Jurisdiction.This study uses sociological legal research methods, namely research that wants to seethe correlation between law and society with the gap between das sollen and das sein, datasources are primary data and secondary data consisting of primary legal material,secondary legal material and tertiary legal material. Data collection techniques in this studyare interviews, questionnaires and literature studies as well as data analysis usingqualitative analysis with deductive methods. The respondents were law enforcement officersfrom investigators of sub-directorate V Ditreskrimsus Polda Riau, Riau High Prosecutor'sOffice, and also the Pekanbaru District Court.The results of this research are Law Enforcement on gambling cases through onlinesites in the Riau Regional Police Jurisdiction, including Intelligence Information Collection,Initial Investigation, Formation of Investigation Team, Evidence Collection, Arrest andSeizure, In-depth Investigation, Legal Prosecution, Courts and Verdicts, Execution ofVerdicts, Prevention and Education. And the inhibiting factors include technological factorsand the skills of the apparatus which result in difficulties in identifying who owns the site,then operational cost factors, law enforcement factors, and community factors. The effortsthat have been made are Improving Technology and Skills, Cross-Border Cooperation,Improving Laws and Regulations, Using Advanced Technology, Collaboration with thePrivate Sector, Raising Community Support, and Providing Additional Resources.Keywords: Law Enforcement, Online Gambling Sites, Riau Regional Police